Meningkatkan Kemampuan Membaca Siswa dengan Metode Speed Reading pada Mata Pelajaran Bahasa Indonesia di Kelas IV SD Hikmah Fajar Waringin Jaya - Imas Kania Rahman; Lutfiyah Lutfiyah; Suyud Arif (AS-SABIQUN, 2022)
As an ability, skill or strength, reading is a process done to understand the mssage delivered by the author via written language. Indonesia language is teaching students about Indonesian language sjills. This research seeks to enhance the reading ability of SD Hikmah Fajar In Indonesian subjects and also to evaluate the students’ reading ability in Indonesian subjects after using the speed reading method. This research with 3 (three) cyckes which are planning, implementation of observation and reflection. Minimum complatenes criteria (KKM) 70. Tehe research subjects were 12 srudents of grade IV SD Hikmah Fajar Waringin Jaya. Data collection techniques used are observation, questionnaires and tests. Instruments used in this study are in the form of questionnaires, student learning outcomes assessment tools and evaluation test. The findings revealed that speed reading method in leaningindonesian in the fourth grade oh Hikmah Fajar elementary school can improve students reading skills. This must be proven from the results obtained by students before implementing speed reading method of 56.25 in the first cycle test, the secore is 72.5. in the next cycle got a of 80.9 and the last score was 95.8 eith very valid criteria